Empowerment of "meronce" hand crafts through training of on-line marketing strategy in the order to increase the income of the family in the village of Merawan Dolok, Dolok Merawan, district, on-line market - Badaruddin; Revida, Erika; Sudarwati, Lina (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The "Melati" Joint Business Group is a group of women's skills including the "Meronce" craftsmanship whose members consist of women in Dolok Merawan Village, Dolok Merawan District, Serdang Bedagai Regency, North Sumatra Province. The results of the 2018 community service program for this business group have shown quite encouraging results, in which this joint business group has been able to increase its organizational capacity and be able to improve its "meronce" handicraft skills by producing products of economic value. However, the "Melati" Joint Business Group is experiencing difficulties in marketing its handicraft products, because so far the method of selling products is still conventional, and they have not been able to market their products online. This community service activity aims to train the "Melati" Joint Business Group in relation to the online marketing strategy of the "Meronce" handicraft products. To achieve these objectives, the service methods used are lecture and discussion techniques, training on the promotion of handicraft products online by providing promotional tools, namely smartphones and equipment, and strengthening group organizations with on-line marketing strategy training. The results of the service activities show that KUBE Melati members already have the ability to market their craft products online such as Facebook and WhatsApp, and there are even consumers who order online. This is enough to motivate them so that they do not feel left behind by the progress of Information Technology in marketing their handicrafts. But they still hope that the service team can provide assistance for them in accordance with the progress of the Information Technology.